Nursing Personnel's Caring Behaviors during End-of-Life Treatment in a Tertiary Care Hospital (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: The standard of end-of-life care has become an important indicator of a hospital's general care standards in modern times. Unfortunately, the present nursing standards and level of care provided to patients reaching the end of their lives fall short of what they had hoped for. As a consequence, it's crucial to look at how caregivers demonstrate care. Therefore, this observational study aims to assess the caring behavior towards death and dying among nursing personnels. MATERIALS AND METHODS: The research design adopted for the study was descriptive research design on 50 nursing personals working in the MICU, SICU, CCU, ITUs and wards working at SJMCH, Bangalore. Purposive sampling technique adopted to select nursing personals and participatory approach using observational rating scale during end of life care was used to assess the caring behaviour. The data was analysed using descriptive and inferential statistics. RESULTS: The result showed that caring behaviour of nursing personnel during end of life care found to be 58.0% with moderate caring behaviour, 38.0% with good caring behaviour and 4 % with poor caring behavior. There is no statistically significant association of caring behaviour of nursing personnel with the baseline variables like age of staff nurses and patients. CONCLUSIONS: It was found that there was no significant difference between demographic variables and caring behavior in nursing personnel. This study depicts that the caring behaviour of nursing personnel during end of life care was found as 58% with moderate caring behaviour, 38% with good caring behaviour and 4 % with poor caring behaviour.